2017
DOI: 10.1002/jcb.26010
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Loganin on MPTP‐Induced Parkinson's Disease Mice: Neurochemistry, Glial Reaction and Autophagy Studies

Abstract: Parkinson's disease (PD) is a progressive neurodegenerative disease, involving resting tremor and bradykinesia, for which no recognized therapies or drugs are available to halt or slow progression. In recent years, natural botanic products have been considered relatively safe, with limited side effects, and are expected to become an important source for clinical mediation of PD in the future. Our study focuses on the ability of loganin, a compound derived from fruits of cornus, to mediate neuroprotection in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 54 publications
1
40
0
Order By: Relevance
“…Loganin is a glucose‐lowering botanic compound (He et al, ), and we previously reported its neuroprotection‐mediated activation of IGF‐1R signaling in motor neurons (Tseng et al, ). Recently, the potential protection of loganin has been revealed in different experimental models of PD (Xu et al, ; Yao et al, ). In this study, we demonstrated that loganin protects neuron against MPP + ‐induced apoptotic death, neurite damage, and oxidative stress, and activations of IGF‐1R and GLP‐1R play the important roles in the neuroprotective effects of loganin (Figure ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Loganin is a glucose‐lowering botanic compound (He et al, ), and we previously reported its neuroprotection‐mediated activation of IGF‐1R signaling in motor neurons (Tseng et al, ). Recently, the potential protection of loganin has been revealed in different experimental models of PD (Xu et al, ; Yao et al, ). In this study, we demonstrated that loganin protects neuron against MPP + ‐induced apoptotic death, neurite damage, and oxidative stress, and activations of IGF‐1R and GLP‐1R play the important roles in the neuroprotective effects of loganin (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…Loganin has been proved to possess glucose‐lowering ability in diabetic mice (He et al, ) and is suggested as a valuable supplement for the treatment of diabetes mellitus and diabetes complications (He et al, ; Jiang, Zhang, Hou, & Zhu, ; Yamabe et al, ). Growing evidence from several cellular and animal models of neurodegenerative disorders demonstrates the potential neuroprotective effects of loganin in PD (Xu et al, ; Yao et al, ). However, whether loganin exerts protective effects on PD and the underlying mechanisms are still not well defined.…”
Section: Introductionmentioning
confidence: 99%
“…Loganin, an iridoid glycoside found in traditional Chinese medicines, such as Flos lonicerae , Fruit cornus , and Strychonos nux vomica , has been reported to regulate immune function and has anti-inflammatory and anti-shock effects. In a mice model, Loganin exerts neuroprotective effects on MPTP-treated mice by decreasing inflammation, autophagy, and apoptosis ( Xu, Cui, et al., 2017 ). Loganin prevented both the loss of dopaminergic neurons and the defect of locomotor activity induced by MPTP in zebrafish larvae, possibly through the suppression of PI3K/Akt/mTOR axis and JNK signaling pathways ( Yao et al., 2017 ).…”
Section: Animal Modelsmentioning
confidence: 99%
“…There is an increase in the level and activity of c-Abl in human and mouse brains under PD conditions, which is evidently found in both the substantia nigra and striatum ( Ko et al, 2010 ; Imam et al, 2011 , 2013 ; Hebron et al, 2013a ; Brahmachari et al, 2016 ). Experimental evidence has demonstrated that, in PD conditions, over-activation of c-Abl might induce parkin dysfunction ( Imam et al, 2011 ; Gonfloni et al, 2012 ; Dawson and Dawson, 2014 ), a-synuclein aggregation ( Hebron et al, 2013a ; Mahul-Mellier et al, 2014 ; Brahmachari et al, 2016 ), and impaired autophagy of toxic elements ( Ertmer et al, 2007 ; Yogalingam and Pendergast, 2008 ; Xu et al, 2017 ), leading to the death of the nigral dopaminergic cells. Accordingly, systemic administration of c-Abl inhibitors (e.g., imatinib and nilotinib) may hold promise for protection against the degeneration of nigral dopaminergic cells in PD and further antiparkinsonian effects ( Hebron et al, 2013a , b ; Karuppagounder et al, 2014 ; Wu et al, 2016 ; Zhou et al, 2017 ; Abushouk et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%